FORMULASI PEMBUATAN PERMEN JAHE UNTUK MENINGKATKAN KETAHANAN FISIK LANSIA - Wati Sukmawati; Ari Widayanti (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity was carried out in the village of Dukuh Jeruk, this activity was a continuation of ginger processing. The partner of this activity is the Ginger SMEs which produce ginger powder drinks. At this time, researchers developed an innovation from processed ginger into ginger candy with the aim that ginger products can be consumed more practically. This ginger candy product has the main raw material of ginger. This service activity was attended by 25 participants who were carried out face-to-face. This activity begins with the preparation of proposals, taking care of licensing to partners, site surveys, preparation of tools and materials, implementation, and analyzing the findings of the activities. This activity is carried out from the beginning of the activity to the end it takes four months. The method used by researchers in this activity is by assisting the processing of ginger candy. The result of this activity is an increase in the knowledge and skills of participants in making ginger candy. Based on the observations, the participants were very enthusiastic about participating in this service activity and it was hoped that the sweets could be enjoyed by the elderly. The elderly who are the target of the activity can enjoy ginger practically and feel the benefits of ginger easily to maintain physical endurance.